Insight into the development of versatile dentin bonding agents to increase the durability of the bonding interface - Porto, Isabel Cristina Celerino de Moraes; Lôbo, Teresa de Lisieux Guedes Ferreira; Rodrigues, Raphaela Farias; Lins, Rodrigo Barros Esteves; da Silva, Marcos Aurélio Bomfim (Frontiers in Dental Medicine, 2023)
Despite the huge improvements made in adhesive technology over the past 50 years, there are still some unresolved issues regarding the durability of the adhesive interface. The utter sealing of the interface between the resin and the dentin substrate remains difficult to achieve, and it is doubtful that an optimal interdiffusion of the adhesive system within the demineralized collagen framework can be produced in a complete and homogeneous way. In fact, it is believed that the hydrolytic degradation combined by the action of dentin matrix enzymes destabilizes the tooth-adhesive bond and disrupts the unprotected collagen fibrils. And while a sufficient resin-dentin adhesion is usually achieved immediately, the bonding efficiency declines over time. Thus, this review will be carried out through a bibliographic survey of scientific articles published in the last years to present strategies that have been proposed to improve and/or develop new adhesive systems that can help to prevent degradation at the adhesive interface. Focusing specially on new clinical techniques or new materials with characteristics that contribute to increase the durability of adhesive restorations, and avoid the recurrent replacement restorative cycle and the consequent increase in damage to the tooth.